Sustainable Innovations in Textile Chemistry and Dyes - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book details two elements of textile chemistry namely- sustainable/eco-friendly dyes and green chemistry. It presents latest topics in sustainable dyeing techniques, low impact dyeing methods, wool dyeing techniques and green chemistry. Certain case studies are also highlighted.
Sustainable Dyeing Techniques -- Low Impact Dyeing Methods for Cotton Using Reactive Dyes -- Eco friendly approaches in wool dyeing - a review of the recent research trends -- Green Chemistry in Textiles -- Eco-friendly dyes/colors.
Keywords: Manufactures; Materials -- Analysis; Chemistry, Technical; Sustainability; Business logistics; Industrial engineering; Production engineering; Machines, Tools, Processes; Characterization and Analytical Technique; Industrial Chemistry; Sustainability; Supply Chain Management; Industrial and Production Engineering